Evaluation of different substrates for the cultivation of Ganoderma lucidum - Kapoor, Pooja; Sharma, B M; Thakur, Renu (Mushroom Research, 2017)
Ganoderma lucidum (W. Curt: Fr.) P. Karst is one of the most popular mushrooms in oriental medicine. In Chinese folklore, fruiting bodies of G. lucidum have been regarded as a panacea for all types of diseases. The present investigations were conducted owing to its commercial medicinal importance and limited study on its cultivation aspects. Two strains of G.lucidum were collected and used in the present study. The cultures of two strains were studied for their radial growth on malt agar medium at different temperatures and pH. Cultivation studies on strain OE-53 of G. lucidum were conducted using different substrate combinations. Malt extract medium, temperature range of 25-35ÚC and acidic pH (5.0) were found conducive for the mycelial growth of G. lucidum. Mango sawdust supplemented with 10 per cent Wheat bran at light intensity 500-800 lux was found to be best in terms of spawn run, primordial initiation, number of primordia, fruit body expansion and development, yield and biological efficiency among all the substrate combinations. The findings of present studies reveal that supplementation of Wheat bran (10%) in Mango sawdust as a base substrate can be used commercially for the cultivation of G. lucidum by the mushroom growers and entrepreneurs.